Guiding Principles to Foster Higher Order Thinking Skills in Teaching and Learning of Mathematics - Mohd Tajudin, Nor’ain; Puteh, Marzita; Adnan, Mazlini (International Journal of Engineering and Technology, 2018)
Stepping into the new millennium, many societies around the world are engaging in serious and promising educational reforms. A holistic framework in the form of a comprehensive process of fostering higher order thinking skills (HOTS) in mathematics teaching and learning is needed to guide teachers in implementation suitable activities in the classroom. Therefore, this research is intended to develop a Guiding Principles of Fostering Higher Order Thinking Skills (GP-HOTS) in teaching and learning of mathematics for secondary school students. The sample of the study was 266 secondary mathematics teachers that were chosen using multilevel cluster sampling technique. An instrument namely the Fostering HOTS Questionnaire related to principles of fostering HOTS in teaching and learning of mathematics was used in this study. Data analyses involved the computation of face, content, reliability indices and validation of themes and items using factor analysis. The results showed that there are six principles of how teachers can foster HOTS in teaching and learning of mathematics namely practice of implementing assessment for learning optimally, practice of determining HOTS learning outcomes, practice of HOTS questioning strategies, practice of integrating Information, Communication and Technology, practice of active learning, and practice of developing habits of mind. These principles have satisfied level of content validity indices as well as revealed an excellent acceptable level of reliability index. The implication is that the developed GP-HOTS in this study can be used in enhancing teachers’ mathematical knowledge for teaching, hence creating futuristic minded students